2010
DOI: 10.1292/jvms.10-0009
|View full text |Cite
|
Sign up to set email alerts
|

Salivary IgA as a Useful Non-Invasive Marker for Restraint Stress in Pigs

Abstract: ABSTRACT. In this study, we investigated the expression of immunoglobulin A (IgA) in porcine salivary gland and its relationship with restraint stress in pigs. IgA was expressed in plasma cells in pig salivary gland, as confirmed by immunohistochemical staining. IgA was also detected in pig saliva itself by ELISA, and salivary IgA levels were increased by a restraint stress. Moreover, there was a circadian rhythm of IgA over the course of a day. These results are the first evidence of IgA expression related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
5
58
1
Order By: Relevance
“…1A). This is consistent with studies on other organs such as salivary glands (Bosch et al, 2001;Takatsuji et al, 2008;Lester et al, 2010;Muneta et al, 2010;Trueba et al, 2012), lacrimal glands of hens (Florence et al, 1995) and rat intestine. Those reports mention that the increase in intestinal IgA levels caused by repeated restraint stress is likely due to the effects of catecholamines on the transport of pIgA across the intestinal epithelium (Reyna-Garfias et al, 2010).…”
Section: Effects Of Acute Stress On Nasal Iga Levelssupporting
confidence: 92%
“…1A). This is consistent with studies on other organs such as salivary glands (Bosch et al, 2001;Takatsuji et al, 2008;Lester et al, 2010;Muneta et al, 2010;Trueba et al, 2012), lacrimal glands of hens (Florence et al, 1995) and rat intestine. Those reports mention that the increase in intestinal IgA levels caused by repeated restraint stress is likely due to the effects of catecholamines on the transport of pIgA across the intestinal epithelium (Reyna-Garfias et al, 2010).…”
Section: Effects Of Acute Stress On Nasal Iga Levelssupporting
confidence: 92%
“…Muneta et al (2010) reported that the IgA concentration in porcine saliva was greater during 1 h of acute immobilization stress. In another study, during a period of intense resistance training in male weightlifters, salivary IgA were greater than that in the recovery stage (Tsai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…CgA is not affected by age, gender or circadian rhythms [81]. This could be considered as an advantage compared with other stress biomarkers such as cortisol [82, 83], or Ig A [84] which are both influenced by these factors.…”
Section: Biomarkers Of Stress Studied In Pigsmentioning
confidence: 99%